Pengembangan Buku Ajar Mata Pelajaran Korespondensi Semester Genap Kelas X Program Otomatisasi Tata Kelola Perkantoran di SMKN 1 Bangkalan - Afifiya Afifiya; Triesninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
Research on the development of textbooks of correspondence subject in the even semester class X regarding office management automation sistem at SMKN 1 Bangkalan to study the program of develop textbooks, discuss the visibality of book, student for textbooks developed by researchers and being studied by, existing textbooks at SMK 1 Bangkalan, and which have been developed by researchers.  This research is a Research and Development (R&D) study with a development bentuk from Borg and Gall that is approved up to 7 stages: potential and problems, combining data, product design, design validation, design revision, product testing, product revision/final product. The subject of the study is a comparison of 20 students of X class majoring in a office administration education study sistem at SMK N 1 Bangkalan. The products show the visability of textbooks material expertss obtained a percentage of 94,4% with very forceful criteria, by linguists obtained a percentage of 91,4% with very forceful criteria, and by graphic experts of 84.8% with very forceful criteria.  From the overall products of expert validation obtained a percentage of 90,2% with very forceful criteria.  While the products of evaluations of obtained an average of 81% with very forceful criteria.  So can be concluded textbooks of correspondence subject on the even semester developed are declared to be very suitable to be used as teaching materials at SMK N 1 Bangkalan.